2013
DOI: 10.5114/wo.2013.33767
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the BRCA1 c.68_69delAG (BIC: 185delAG) mutation in women with breast cancer from north-central Poland and a review of the literature on other regions of the country

Abstract: Aim of the studyGermline mutations in BRCA tumor suppressor genes are strongly associated with breast and ovarian cancer. The lifetime risk of these cancers in women with BRCA1 mutation is 84% and 27%, respectively.Studies on the prevalence of BRCA1 c.68_69delAG congenital mutation, the most frequent in Ashkenazi Jews, among women with breast cancer from north-central Poland and review of the literature on other regions of the country. Evaluation of the c.68_69delAG association with breast cancer risk, with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Similarly, a study from north-central Poland reported that the c.68_69delAG mutation was rare in their population, detected only in one out of 252 BC patients screened. Consequently, Hartwig et al (2013) recommended that the c.68_69delAG mutation should not be part of the primary BRCA1 screening test in the population of north-central Poland.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a study from north-central Poland reported that the c.68_69delAG mutation was rare in their population, detected only in one out of 252 BC patients screened. Consequently, Hartwig et al (2013) recommended that the c.68_69delAG mutation should not be part of the primary BRCA1 screening test in the population of north-central Poland.…”
Section: Discussionmentioning
confidence: 99%
“…The common germline mutations within this gene are the c.68_69delAG (185delAG) located in exon 2 and the c.5266dupC (5382insC) located in exon 20. The two germline mutations were first described as founder mutations in Ashkenazi Jews (Roa et al 1996), though they are also reported in other ethnic groups in Europe (Hartwig et al 2013, Pogoda et al 2020), Asia (Chakraborty et al 2013, America (Ewald et al 2011, Rummel et al 2017), and Northern Africa (Abdel-Mohsen et al 2016, Abou-El-Naga et al 2018, Mahfoudh et al 2019. Individuals harboring these mutations are at elevated risks of BC, OC, prostate cancer, and other cancers (Barrios et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BRCA1 breast cancer susceptibility protein is used by the cell in an enzymatic pathway which repairs DNA molecules that have double stranded breaks (National Center for Biotechnology Information [NCBI], 2018). Besides DNA repair, it is involved in cell cycle control and regulation of apoptosis (Hartwig et al, 2013). Exon2 is one of the most common mutation sites in BRCA1 gene for c.68-69delAG (BIC: 185delAG) frameshift mutation which occurs in codon 23 of exon2, that results in the creation of stop codon which leads to premature termination of translation and significant truncation of protein, and is associated with the severity of the disease like early onset, bilaterality of breast cancer (Hartwig et al, 2013;Chakraborty et al, 2015).…”
Section: Research Articlementioning
confidence: 99%
“…Besides DNA repair, it is involved in cell cycle control and regulation of apoptosis (Hartwig et al, 2013). Exon2 is one of the most common mutation sites in BRCA1 gene for c.68-69delAG (BIC: 185delAG) frameshift mutation which occurs in codon 23 of exon2, that results in the creation of stop codon which leads to premature termination of translation and significant truncation of protein, and is associated with the severity of the disease like early onset, bilaterality of breast cancer (Hartwig et al, 2013;Chakraborty et al, 2015). The majority of breast cancers occur before age fifty (50) in most South Asian countries and it is supposed to cause by protein truncating mutations (nonsense mutation) in BRCA (Hopper et al, 1999;Liede and Narod 2002).…”
Section: Research Articlementioning
confidence: 99%